P02 | THE C-C CHEMOKINE-RECEPTOR 2 (CCR2)/CCL2 AXIS PARTICIPATE IN PLATELET FUNCTION IN MYELOFIBROSIS (European Journal of Histochemistry)
Myelofibrosis (MF) is the most severe myeloproliferative neoplasm driven by mutations of the MPL/JAK2 axis induced by megakaryocytes (MKs) with reduced GATA1 content1. The proinflammatory milieu in the bone marrow (BM) microenvironment favors the disease evolution, by sustaining BM fibrosis, hematopoietic failure and extramedullary hematopoiesis2. The CC Chemokine 2 (CCL2) is an immune-modulatory cytokine highly expressed in MF, exerting its biological function by engaging the CCR2 receptor, by regulating the MAPK/ERK, PI3K/Akt, and JAK/ STAT pathways. The CCR2 increased expression was detected on CD34+ hematopoietic stem cells (HSC) isolated from MF patients. The percentage of CD34+CCR2+ cells parallels the degree of BM reticular deposition in overt-MF vs Pre-MF, suggesting that CCR2 expression can be used to track the fibrotic changes in MPN disease progression. The GATA1 modulatory function in the transcription of CCR2 was confirmed by the correlation between the GATA1 hypo-expression and the CCR2 overexpression in the HSC compartment isolated from MF patients. In addition, BM samples from patients with MF showed that GATA1 negative MKs had an increased expression of CCR2. The morphological observation on BM samples from MF patients highlighted the increased CCR2 expression in the cytoplasm of MKs, mostly arranged in aggregate-like structures. Both P-selectin staining and TEM observations confirmed the platelet aggregation in the MF patients, suggesting the CCR2 involvement in the residual platelet function in MF. In line with the abnormal MK phenotype, recent proof indicates that myeloproliferative disorders are associated with a high incidence of arterial and venous thrombotic events3. Finally, Ruxolitinib rescue the MKs maturation, by down regulating the CCR2 expression and restoring the platelet production. In conclusion, our result showed that CCR2 is highly expressed in MKs in MF, and the CCR2/CCL2 axis might exert several biological functions in MF progression and contribute to secondary complications.